Penerapan Model Pembelajaran Bahasa Arab Berbasis SAVI (Somatis, Auditori, Visual, Intelektual) dalam Meningkatkan Hasil Belajar pada Peserta Didik - Koderi, Koderi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2018)
Abstract: This research is focused on  to cope with the problems commonly encountered by students in learning Arabic including low retention, low motivation, lack of skills and unsatisfactory learning achievement due to insufficient learning facilities and variations.  This study is aimed at acquiring  obtaining empirical data "The influence of Arabic language-based learning model SAVI (somatic visual auditory intellectual) in improving the learning outcomes of students of class VIII in MTs Negeri 2 Bandar Lampung in 2016/2017". This study is a quasi-experimental research (quasi experimental research). Based on the analysis of homogeneity is known that both data result of learning the Arabic language learners class VIII G (experimental class) and the result of learning the Arabic language learners class VIII F (control group) have the same variance (homogeneous). So as to test the hypothesis can be used t-test. The calculation result obtained using t-test, t-test = 4.698 and of the distribution table at significant level known ttabel = 2.00 therefore thit> ttable.The results of these calculations at the same time also shows that the application of the model of learning Arabic based SAVI can significantly affect the learning outcome Arabic language learners because learning model Arabic-based SAVI can make students more creative, independent, more active and feel unfettered in the learning process in the classroom. Keywords: Arabic, Learning, Models, SAVI